A Mentoring-Coaching to Improve Teacher Pedagogic Competence: An Action Research - Ina Fatina Dewi (STKIP Singkawang, 2021)
The purpose of this research is to boost teacher pedagogic competence using a mentoring-coaching approach. Three SMPK Immanuel Pontianak teachers participated in the two cycles of action research conducted in the year academic of 2014-2015. This recent research inspects the impact of principal’s approaches on teacher pedagogic competence changes and its hindering factors. The principal’s approaches toward teachers were decided using a Glickman’s diagram, and teacher performance was measured using a rubric to measure their teaching performance. The collected data were analyzed qualitatively and quantitatively. The findings indicated that teacher pedagogic was able to rise using this combined technique, although not all subjects were successful in being improved. The other significant findings were (1) the principal’s consistency in applying chosen approach, (2) teachers’ ability to identify their need for improvement. This recent study’s limitations were the minimal number of participants, teacher motivation as the overlooked factor, and the supervisor’s ability to consistently apply the chosen approaches.